2015
DOI: 10.1111/pai.12387
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity alters immune cell frequencies and responses in umbilical cord blood samples

Abstract: These results support the hypothesis that maternal obesity influences programming of the neonatal immune system, providing a potential link to increased incidence of chronic inflammatory diseases such as asthma and cardiovascular disease in the offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
87
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 22 publications
9
87
4
Order By: Relevance
“…The percentage change in estimates between models using the adult and cord blood reference panels was under 10% at 14/15 sites using the Andrews Table S8). Although maternal BMI was not associated with estimated cell proportions in our data, others have observed that maternal BMI is associated with cord blood cellular heterogeneity (31,32), in addition, some random variability in cell distribution across the range of maternal BMI can be expected. Therefore, we believe that adjustment is appropriate and indeed necessary.…”
Section: à7contrasting
confidence: 85%
“…The percentage change in estimates between models using the adult and cord blood reference panels was under 10% at 14/15 sites using the Andrews Table S8). Although maternal BMI was not associated with estimated cell proportions in our data, others have observed that maternal BMI is associated with cord blood cellular heterogeneity (31,32), in addition, some random variability in cell distribution across the range of maternal BMI can be expected. Therefore, we believe that adjustment is appropriate and indeed necessary.…”
Section: à7contrasting
confidence: 85%
“…Future studies will need to focus on epigenetic changes within individual immune cell populations, as important changes in small populations may not be apparent when analyzing total leukocytes. Specifically, it might be interesting to examine epigenetic changes in monocytes or CD4 T helper cells as we have shown recently a dampened response by monocytes and myeloid dendritic cells stimulated by TL4 or TLR1&2 agonists and a reduction in IL-4 production by CD4 T cells (110). …”
Section: Resultsmentioning
confidence: 99%
“…Maternal obesity leads to changes in immune cell counts –including eosinophils and monocytes, the levels of inflammatory cytokines (i.e. interleukin [IL]-1β, IL-6, tumor necrosis factor [TNF]-α, or interferon [IFN]-α2) 22,23 , and lipid profiles in cord blood or early post-natal life 25 . Moreover, maternal obesity may lead to metabolic and oxidative alterations in the placenta and the fetus 24 , and increased leptin level and insulin resistance in newborns 26 .…”
Section: Maternal Obesity During Pregnancy and Weight Gain In Early Pmentioning
confidence: 99%